The use of cluster analysis in entrepreneurship research: Review of past research and future directions. (4th July 2022) - Crum, Michael; Nelson, Thomas; de Borst, Johan; Byrnes, Paul
ABSTRACT: Cluster analysis (CA) has been used in many diverse disciplines to develop classifications or taxonomies. In the entrepreneurship literature, cluster analysis has been used to test theory as well as to develop new theory, for example, by creating taxonomies of types of entrepreneurs, firms, and business strategies. This paper reviews the major studies using clustering techniques in top entrepreneurship focused journals from 1990–2019. The data show that cluster analysis is being used less frequently in the entrepreneurship field. Some suggestions for how and where it can be appropriately used in future research are provided.